2011
DOI: 10.1210/en.2011-0067
|View full text |Cite
|
Sign up to set email alerts
|

ERK-Regulated Double Cortin-Like Kinase (DCLK)-Short Phosphorylation and Nuclear Translocation Stimulate POMC Gene Expression in Endocrine Melanotrope Cells

Abstract: We tested whether double cortin-like kinase-short (DCLK-short), a microtubule-associated Ser/Thr kinase predominantly expressed in the brain, is downstream of the ERK signaling pathway and is involved in proopiomelanocortin gene (POMC) expression in endocrine pituitary melanotrope cells of Xenopus laevis. Melanotropes form a well-established model to study physiological aspects of neuroendocrine plasticity. The amphibian X. laevis adapts its skin color to the background light intensity by the release of α-MSH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…This finding is consistent with the observation that DCLK2 enters the nucleus after the cleavage of its C-terminus (a probable ‘regulatory domain’) ( Nagamine et al , 2014 ). Translocation from the cytoplasm to the nucleus has also been suggested for DCLK1 ( Burgess and Reiner, 2001 ; Kuribara et al , 2011 ). Autophosphorylation assays suggested that a DCLK3 protein with an apparent molecular weight close to that of the full-length form had the highest level of catalytic activity.…”
Section: Discussionmentioning
confidence: 96%
“…This finding is consistent with the observation that DCLK2 enters the nucleus after the cleavage of its C-terminus (a probable ‘regulatory domain’) ( Nagamine et al , 2014 ). Translocation from the cytoplasm to the nucleus has also been suggested for DCLK1 ( Burgess and Reiner, 2001 ; Kuribara et al , 2011 ). Autophosphorylation assays suggested that a DCLK3 protein with an apparent molecular weight close to that of the full-length form had the highest level of catalytic activity.…”
Section: Discussionmentioning
confidence: 96%
“…In these studies we used U0126 to demonstrate a link between MEK1/2 cascade inhibition and DCLK1 expression in human pancreatic cancer cells and confirmed our results with microarray data generated by other groups in treated colon cancer cell lines (Figure  4D & Additional file 1: Figure S2F). Additionally, a previous paper demonstrated that nuclear translocation of phosphorylated DCLK1-short is attenuated in U0126-treated Xaenopus laevis melanotrope cells [46], which if broadly applicable, implies that MEK1/2 cascade inhibition has the potential to limit or prevent DCLK1-based intracellular signaling. The data from this study and our previous studies [7,8] suggest that DCLK1 interacts with and regulates the MAPK/ERK effector c-MYC.…”
Section: Discussionmentioning
confidence: 99%
“…A rabbit polyclonal antibody was commercially generated (Abbomax) to target ser-30(β)/336(α), which has previously been demonstrated to be phosphorylated, against a 15 amino acid peptide sequence similar to others previously used to generate phospho-DCLK1 antibodies [46,55]. To confirm specificity, ELISA was performed using phosphospecific and non-phosphospecific peptide.…”
Section: Methodsmentioning
confidence: 99%
“…Similar results were observed in the protein analysis by WB. In all populations, it was observed a 82kDa band corresponding to the most studied isoform from previous studies (23). Fig.1A show the expression of DCLK1 protein in pCCA-subpopulation compare to unsorted pCCA cells.…”
Section: Expression In Vitromentioning
confidence: 54%
“…In all populations, a 82‐kDa band was observed, corresponding to the most studied isoform from previous studies. ( 23 ) Figure 1A shows the expression of DCLK1 protein in the pCCA subpopulation compared with unsorted pCCA cells. The pCCA LGR5+ (1.41 ± 0.2; n = 6; P < 0.01), pCCA CD90+ (0.68 ± 0.07; n = 6; P < 0.05), pCCA 133+ (0.74 ± 0.07; n = 6; P < 0.01), pCCA EpCAM+ (1.15 ± 0.19; n = 6; P < 0.01;), and pCCA CD13+ (1.3 ± 0.03; n = 6; P < 0.01) expressed higher protein levels compared with the unsorted control (0.45 ± 0.14; n = 6).…”
Section: Resultsmentioning
confidence: 99%